Effect of grinding media size and shape on the iron mill scale particle and properties - Che Wan Noorakma Abdullah (Universiti Malaysia Perlis, 2008)
A study was undertaken to determine how the effect of grinding media size and shape on the iron mill scale particle size and properties. Comparative tests were conducted using the two types of grinding media which are cylindrical porcelain with the 3 sizes (Ø 3.19 x 3.185cm, Ø 2.05 x 2.1cm , Ø 1.32 x 1.33cm) and spherical steel ball (Ø 2.5cm) in laboratory roll mill at various conditions of equality such as media mass, size combination distribution, surface area and volume. The laboratory test was run at twelve experiments with the difference combination of size and shape of grinding media. During the milling process, the speed and time of roll mill were fixed constantly at 230.7 rpm and 4 hours for every milling process respectively. After milling, the ground particle of iron mill scale was analyzed and characterized by four analyses including morphology analysis by Scanning Electron Microscope, particle size analysis by Particle Size Analyzer, the surface area and porosity by Braunauer Emmet Teller and also the phase identification by X- ray Diffraction and Energy Dispersive X-ray. The laboratory results indicated that combination size of cylindrical porcelain media produce a product with slightly less oversize due to their greater surface area, but essentially the same sizing at the fine end as that produces with the steel balls medium. The reason may be that the advantage of greater surface area is balanced by the line contact and area contact grinding action with the cylindrical porcelain. It also was found that the morphological of ground product of cylindrical porcelain is modular and irregular shape while the ground product of sphere steel ball give the morphology shape as flaky and spongy which could effect to mechanical properties of powder metallurgy product.